2017
DOI: 10.1186/s12957-017-1238-9
|View full text |Cite
|
Sign up to set email alerts
|

Detection rate of prostate cancer following biopsy among the northern Han Chinese population: a single-center retrospective study of 1022 cases

Abstract: BackgroundProstate cancer is known to have ethnic and regional differences. The study aimed to clinically evaluate the detection rate of prostate cancer on transrectal ultrasonography (TRUS)-guided prostate biopsy and analyze its characteristics among the northern Han Chinese population at a single center.MethodsBetween October 2009 and September 2016, a total of 1027 Chinese men, who had undergone TRUS-guided prostate biopsy at Qingdao Municipal Hospital, were retrospectively analyzed. Prostate biopsies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…Similar to our study the significant number of patients had advanced cancer at initial diagnosis. [ 11 ] Our study and study by Gupta et al show a similar cancer detection rate and is comparable with the western and Asian literature[ 6 ] [ Table 4 ].…”
Section: Discussionsupporting
confidence: 90%
“…Similar to our study the significant number of patients had advanced cancer at initial diagnosis. [ 11 ] Our study and study by Gupta et al show a similar cancer detection rate and is comparable with the western and Asian literature[ 6 ] [ Table 4 ].…”
Section: Discussionsupporting
confidence: 90%
“…The higher threshold was set to offset the biases that may be associated with PSA values. PSA values above 10 ng/ml have high speci city in prostate cancer diagnosis [16,17].…”
Section: Case De Nition By Total Psa Thresholdsmentioning
confidence: 99%
“…[ 11 12 13 ] The extended 12-core biopsy template increases the detection rate of prostate cancer and decreases the probability of repeat biopsy when compared to the sextant protocol. [ 14 ] Jia et al [ 15 ] in a study done among the Han people of China, reported prostate cancer detection rate of 42.8% following a 10-core (plus an additional core in each suspicious area) biopsy protocol. Furthermore, Ojewola[ 16 ] in South-western Nigeria, reported an overall cancer detection by the extended technique as 48.8%.…”
Section: Introductionmentioning
confidence: 99%